2019
DOI: 10.3390/pr7100751
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Insights into the Mechanism for Gas Separation through Nanochannels in 2D Laminar MXene Membranes

Abstract: Clarifying the mechanism for the gas transportation in the emerging 2D materials-based membranes plays an important role on the design and performance optimization. In this work, the corresponding studies were conducted experimentally and theoretically. To this end, we measured the gas permeances of hydrogen and nitrogen from their mixture through the supported MXene lamellar membrane. Knudsen diffusion and molecular sieving through straight and tortuous nanochannels were proposed to elucidate the gas transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Not only are outstanding gas separation properties of membranes essential but also is their long-term stability required for use in industry. Therefore, long-term stability of MXene membranes in gas separation performance was tested by several studies in the order of hours, days, and weeks. , ,,,,, Ding et al reported that the MXene membrane displayed stable performances with H 2 and CO 2 permeability of ∼2210 and ∼15.9 Barrer, respectively, and H 2 /CO 2 selectivity of ∼147 up to 70 h with shifting between a dry and wet (3 vol % steam) equimolar H 2 /CO 2 mixture at 25 °C and 1 bar. More importantly, to confirm high temperature durability of MXenes, Fan et al applied long-term permeation measurements for H 2 /N 2 separation at 320 °C and reported stable H 2 permeance of 612 GPU and the H 2 /N 2 mixture selectivity of 41 during 200 h. Shen et al suggested that as-prepared MXene with a thickness of 0.02 μm and functionalized MXene with borate and poly­(ether imide) (PEI) preserved their separation performances of H 2 /CO 2 and CO 2 /CH 4 within 100 h at 1.5 bar and 25 °C, respectively.…”
Section: Gas Separationmentioning
confidence: 99%
“…Not only are outstanding gas separation properties of membranes essential but also is their long-term stability required for use in industry. Therefore, long-term stability of MXene membranes in gas separation performance was tested by several studies in the order of hours, days, and weeks. , ,,,,, Ding et al reported that the MXene membrane displayed stable performances with H 2 and CO 2 permeability of ∼2210 and ∼15.9 Barrer, respectively, and H 2 /CO 2 selectivity of ∼147 up to 70 h with shifting between a dry and wet (3 vol % steam) equimolar H 2 /CO 2 mixture at 25 °C and 1 bar. More importantly, to confirm high temperature durability of MXenes, Fan et al applied long-term permeation measurements for H 2 /N 2 separation at 320 °C and reported stable H 2 permeance of 612 GPU and the H 2 /N 2 mixture selectivity of 41 during 200 h. Shen et al suggested that as-prepared MXene with a thickness of 0.02 μm and functionalized MXene with borate and poly­(ether imide) (PEI) preserved their separation performances of H 2 /CO 2 and CO 2 /CH 4 within 100 h at 1.5 bar and 25 °C, respectively.…”
Section: Gas Separationmentioning
confidence: 99%
“…As shown in Figure 9b, the MXene membrane structure (e.g., interlayer distance and intercalating water) significantly influence the gas diffusion, including the mechanism, diffusivity, and selectivity. 303,309 The structure of nanopores, the chemical properties and the layer of the 2D materials, and the addictive are commonly used to strengthen the gas separation efficiency. Previous investigations have shown that chemical functionalization of the graphene sheet can increase the absorption ability of CO 2 , while the functionalization of pores rim can significantly improve the selectivity of CO 2 over N 2 .…”
Section: Gas Separationmentioning
confidence: 99%
“…4 illustrates the SEM images of Ti 3 C 2 T x . 47 2.3.5 Atomic force microscopy (AFM). Atomic force microscopy (AFM) has gained a lot of interest in the Fig.…”
Section: Fourier Transformed Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…4 (a and b) SEM images of cross-section of Ti 3 C 2 T x (c) Top view and (d) low magnification cross section. 47 investigation of 2D materials it can indicate the lateral ake size and thickness. However, one should be mindful of the restrictions while doing AFM investigations because the thickness of 2-dimensional monolayers can vary signicantly based on the presence of various surface adsorbed species and entrapped interfacial molecule, besides the imaging method involved.…”
Section: Fourier Transformed Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%